A Reliable and Effective UPLC-MS/MS Method for the Determination of Oprozomib in Rat Plasma - Xia Li; Ya-nan Liu; En Zhang; Ren-ai Xu; Tingyong Yang; Shunbin Luo (Journal of Analytical Methods in Chemistry)
Oprozomib, as a second-generation orally bioavailable protease inhibitor (PI), is undergoing clinical evaluation for the treatment of haematological malignancies. In relapsed refractory multiple myeloma (RRMM) patients, oprozomib has shown good efficacy as a single agent or combination therapy. In this experiment, our purpose was to validate a sensitive and rapid method for the determination of oprozomib concentration in rat plasma by ultraperformance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). The samples were treated with acetonitrile as the precipitant and separated by gradient elution using a Waters Acquity UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm). Using the selective reaction monitoring (SRM) method, the measurement was finished with the ion transitions of m/z 533.18 ⟶ 199.01 for oprozomib and m/z 493.03 ⟶ 112.03 for tepotinib (internal standard, IS), respectively. Meanwhile, acetonitrile and 0.1% formic acid aqueous solution were used as the mobile phase, and the flow rate was 0.3 mL/min. The lower limit of quantification (LLOQ) of the method was 1.0 ng/mL, and the linear relationship was good in the range of 1.0–100 ng/mL. In addition, the precision of four concentration levels was determined with the values of 3.1–7.3% and the accuracy was from −14.9% to 12.9%. Moreover, the recovery was determined to be from 85.1% to 96.1%, and the values of matrix effect were no more than 110.4%. The optimized UPLC-MS/MS method was also suitable for the pharmacokinetic study of rats after a single oral administration of 21 mg/kg oprozomib.